The modification of arctic permafrost coastlines - Lantuit, Hugues (Prof. Dr.) (2008)
The arctic region is undergoing the most rapid environmental change experienced on Earth, and the rate of change is expected to increase over the coming decades. Arctic coasts are particularly vulnerable because they lie at the interface between terrestrial systems dominated by permafrost and marine systems dominated by sea ice. An increased rise in sea level and degradation of sea-ice as predicted by the Intergovernmental Panel on Climate Change in its most recent report and as observed recently in the Arctic will likely result in greater rates of coastal retreat. An increase in coastal erosion would result in dramatic increases in the volume of sediment, organic carbon and contaminants to the Arctic Ocean. These in turn have the potential to create dramatic changes in the geochemistry and biodiversity of the nearshore zone and affect the Arctic Ocean carbon cycle. To calculate estimates of organic carbon input from coastal erosion to the Arctic Ocean, current methods rely on the length of the coastline in the form of non self-similar line datasets. This thesis however emphasizes that using shorelines drawn at different scales can induce changes in the amount of sediment released by 30% in some cases. It proposes a substitute method of computations of erosion based on areas instead of lengths (i.e. buffers instead of shoreline lengths) which can be easily implemented at the circum-Arctic scale. Using this method, variations in quantities of eroded sediment are, on average, 70% less affected by scale changes and are therefore a more reliable method of calculation. Current estimates of coastal erosion rates in the Arctic are scarce and long-term datasets are a handful, which complicates assessment and prognosis of coastal processes, in particular the occurrence of coastal hazards. This thesis aims at filling the gap by providing the first long-term dataset (1951-2006) of coastal erosion on the Bykovsky Peninsula, North-East Siberia. This study shows that the coastline, which is made of ice-rich permafrost, ...